2006
DOI: 10.1021/jf060808o
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Concentrations of Phenolic Constituents in Cane Sugar Manufacturing Products with Their Antioxidant Activities

Abstract: Polyphenol content and free radical scavenging capacity of seven kinds of sugar manufacturing products (A sugars, clear juices, syrups, massecuite, and A, B, and C molasses) were studied. Seventy-two samples were collected at different stages of the process during two sugar harvests from a local sugar factory (Bois-Rouge, La Réunion). The total phenolic content of sugar products was determined according to the Folin-Ciocalteu assay. Polyphenols of sugar products were extracted with ethyl acetate and quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 25 publications
7
78
0
1
Order By: Relevance
“…Phenolic content was determined using the Folin-Ciocalteu colorimetric method as described by Payet et al (2006) with modification. Briefly, 0.5 mL 0.2 M Folin-Ciocalteu reagent and 0.8 mL 7.5% sodium carbonate solution were mixed with 0.1 mL appropriately-diluted extract.…”
Section: Determination Of Phenolic Contentmentioning
confidence: 99%
“…Phenolic content was determined using the Folin-Ciocalteu colorimetric method as described by Payet et al (2006) with modification. Briefly, 0.5 mL 0.2 M Folin-Ciocalteu reagent and 0.8 mL 7.5% sodium carbonate solution were mixed with 0.1 mL appropriately-diluted extract.…”
Section: Determination Of Phenolic Contentmentioning
confidence: 99%
“…Rum distillate wastewater is generally considered an industrial waste, but it is actually a bio-resource with high mineral and polyphenol content. Sugar manufacturing products such as syrup, bagasse and molasses contain many types of polyphenol compounds [1][2][3][4][5] . It has been reported that numerous bioactive compounds such as phenylglycosides, lignans, lignan glycosides, phenylpropanoids and phenylpropanoid glycosides have been isolated from Kokuto, a traditional Japanese brown cane sugar, and molasses [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant capacity of the feed molasses and the total permeate from the charcoal chemical regeneration was experimentally measured at a pH of 11 using a Hitachi U-2000 spectrophotometer at 517 nm and the DPPH (1-diphenyl-2-picrylhydrazyl) method, according to the method of Cheng et al [1,8,22] with TROLOX as standard. A blank was prepared for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The linear regression coefficients (r) and values for the slope (v) and intercept (%Do) are also summarized in Table 2. A comparison of experiments [4][5][6][7][8][9][10][11] shows that v is mainly affected by the feed pH, with values close to 1 h -1 (from 0.60 to 1.44 h -1 ) for systems with pH 3, whereas %Do depends on the pH, initial NPAC and TMP. This result confirms that, in experiments at pH 3, %D increases with increasing %Do, reaching a maximum value of 95.80 ± 0.02% at a TMP of 100 kPa and initial NPAC concentration of 5 g/L.…”
Section: Operating Conditions For Colour Removal From Beet Molassesmentioning
confidence: 99%
See 1 more Smart Citation